PERAN PEMBELAJARAN KEWIRAUSAHAAN DALAM MENUMBUHKAN MINAT BERWIRAUSAHA MAHASISWA - Ratu, Liliany Purnama; Purwandari, Elce; Iskandar, Erwan; Saleh, Muhammad; Hamidah, Nur (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The attitude, spirit, and ability to create something new that is very valuable and useful for oneself and others is a form of entrepreneurship. The Role of entrepreneurship learning, higher education is intended to be able to form students who have an entrepreneurial mentality, in which there is a spirit of never giving up, good at seeing opportunities, brave to take risks, creative and innovative, apart from that, it can produce graduates who are ready to enter the world of work, and are even able to create jobs. This research aims to determine the growth of students' interest in entrepreneurship at the Al-Azhaar Lubuklinggau Islamic Institute students who have taken entrepreneurship courses using a sample of 56 students as respondents. The method used is quantitative in the form of a survey. Data collection was carried out by distributing questionnaires online in the form of a Google Form with a Likert scale ranging from 1 to 4. Data were analyzed descriptively and quantitatively. The results of the study found that entrepreneurship learning plays a role in fostering student entrepreneurship interest. The research implications emphasize the importance of a holistic entrepreneurial learning approach and practical experience in increasing students' entrepreneurial interest. This highlights the active role that educational institutions can play in preparing students to become successful entrepreneurs and innovate.